The assessment in terms of QBO of NeQuick 2 model - Sagir, Selcuk; Atici, Ramazan; Akalin, Yakup; Yesil, Ali (Elsevier, 2019)
The NeQuick 2 model which is a model calculated to ionospheric parameter was evaluated in terms of the stratospheric QBO. The relationship with QBO of the difference (Delta NmF1) was investigated by the multiple regression analysis model. Delta NmF1 defined as the difference (Delta NmF1 = NmF1(measured) - NmF1(NeQuick 2)) between the measured value from ionosonde and calculated value through the NeQuick 2 model of maximum electron density of the F1 region (NmF1). This investigation showed that the relationship at solar maximum case is stronger than the relationship at solar minimum case both in Darwin and in Learmonth stations. In solar minimum case, there are negative correlations between QBO and Delta NmF1 at both stations. In Darwin station, 67% of Delta NmF1 changes in case of solar maximum, 35% of Delta NmF1 changes in case of solar minimum can arise from the QBO. In Learmonth station, 51% of Delta NmF1 changes in case of solar lmaximum, 30% of Delta NmF1 changes in case of solar minimum can arise from the QBO. The results showed that the addition of QBO to the NeQuick 2 model would allow making calculations closing to actual data especially in the equator region of this model. (C) 2018 National Authority for Remote Sensing and Space Sciences. Production and hosting by Elsevier B.V.
Keywords: NeQuick 2 Model; QBO; Ionospheric F1 region; Electron density